The Influence of Different Arrangements of Shallow Dimples on the Resistance of Plates Subjected to Relative Fluid Motion - Praß, Julian; Wannemacher, Hagen; Franke, Jörg; Becker, Stefan (Technische Mechanik, 2019)
Shallow dimples have long been a scientifically investigated topic to reduce the flow resistance of objects subjectedto overflow. Most of the investigations on the influence of dimples on flow resistance have so far been carriedout experimentally. Although the arrangements and flow conditions are often similar, different research activitiesconclude differently concerning the effect of the surface structures. This also leads to disagreement regarding thecauses of flow resistance reductions. In this paper, time-resolved Large Eddy Simulations on two different, alreadyexperimentally investigated setups of dimples have been carried out to better understand the effects of dimpleson the surface being subjected to relative fluid motion. In one case the dimples were examined in overlappingarrangement, in the other case in a non-overlapping arrangement. We were able to show that the formation ofstreaks near the surface significantly influences the local contribution to the flow resistance. For the overlappingarrangement, only a slight resistance reduction of 0.12 % was determined. For the non-overlapping arrangement,the mean resistance reduction was found to be 3.16 %. Regardless of the resistance reduction determined, a clearinteraction between longitudinal vortices near the plate and local contributions to flow resistance could be demon-strated. Since these longitudinal vortices are directly influenced by the dimples, it is very likely that an optimizedarrangement of the dimples, adapted to the flow conditions, can reduce the resistan
Keywords: drag reduction; passive method; macroskopic surface structures